Green synthesis of metal nanoparticles, their chemical and biochemical characterizations - Jahan, Israt (My University, 2019)
Nanotechnology has been a flourishing field by being concentrated on the fabrication, characterization, manipulation and the exploitation of materials at the nanometre scale. There is also an expanding commercial demand for nanoparticles, particularly the metallic nanoparticles because of their wide-ranging capacity to be used in various sectors. Conventional methods for nanoparticle synthesis are quite expensive as well as they produce nanoparticles with toxic residues. The existence of these contaminated toxic residues with synthesized NPs can create potential risks such as ecological imbalance, carcinogenicity and cytotoxicity which might limit their clinical and biomedical applications. Hence, there is a new branch in contemporary scientific approach which is called nanobiotechnology. Along with the chemical and physical processes, this new scientific branch particularly deals the principles of biology for the production of particles at nano-levels of specific functions. Providing that they utilize simple, moderately low-priced and effortlessly scaled-up nontoxic materials for comparatively a large-scale fabrication, the bio-based techniques for the production of NPs are economic as well as environmentally. Besides, the green syntheses of NPs with microwave-assisted heating technique offer some extra benefits. This is due to the reason that it reveals increased reaction kinetics and boosts reaction rates which eventually accelerate higher yields along with the desirable quality. Considering these facts, scopes and benefits, the main aim of this study has been to fabricate silver and copper nanoparticles via plant extracts, as reducing, capping and stabilizing agents. In this investigation, microwave irradiation scheme with two optimized parameters (time and temperature) has been used for facile and fast phytosynthesis of NPs. Aqueous extracts of Malus pumila (apple) pulp, Cuminum cyminum (cumin) seeds, Zingiber officinale (ginger) rhizome, Rosa santana (rose) petals, Citrus sinensis (orange) peel and Citrus limon (lemon) peel have been used to synthesize AgNPs whereas Camellia sinensis (green tea), Zingiber officinale (ginger) rhizome, Citrus sinensis (orange) juice and Pinus brutia (Turkish pine) bark extracts were used for CuNPs synthesis. After successful syntheses, the quantity and quality of nanoparticles have been screened by UV-Vis spectroscopy, X-Ray Diffraction (XRD) analysis, Fourier Transforms Infrared (FTIR) spectroscopy, Transmission Electron Microscopy (TEM) and particle size distribution and Zeta potential measurement. The TEM micrographs confirmed the presence of nearly spherical or oval shaped nanoparticles (AgNPs & CuNPs). For AgNPs, the smallest size ranged (1.84 - 20.57 nm) nanoparticles (CcAgNPs) with the mean diameter of 14.30 nm were obtained from Cuminum cyminum (cumin) seed extract while the largest size ranged (7.5 - 69.83 nm) nanoparticles (ClAgNPs) with the average diameter of 41.86 nm were found using Citrus limon (lemon) peel extract. On the other hand, for CuNPs, the smallest size ranged (6.93 - 20.70 nm) nanoparticles (CisCuNPs) with the average diameter of 17.58 nm were observed from Citrus sinensis (orange) juice extract and the largest particle size ranged (17.59 - 149.92 nm) nanoparticles (CasCuNPs) with the average diameter of 45.30 nm were achieved from Camellia sinensis (green tea). Antibacterial prospective and potentials of both silver and copper NPs have been investigated against Gram-positive (Staphylococcus aureus) along with Gram-negative (Escherichia coli) bacteria. It has been found that the nanoparticle samples with smallest particle size range and highest potential value showed the best antibacterial activities. Therefore, the silver nanoparticle (CcAgNPs) obtained from Cuminum cyminum seed extract showed the highest antibacterial activity against S. aureus and E. coli with the maximum inhibition zones of 12.53 mm and 10.30 mm in diameter, respectively. Similarly, the copper nanoparticles (CisCuNPs) using Citrus sinensis juice extract showed the maximum antibacterial activity with the highest inhibition zones of 12.60 mm and 10.83 mm in diameter against S. aureus and E. coli, respectively. Considering the overall outcomes, it is remarkable that silver nanoparticles showed stronger antibacterial activity then copper nanoparticles. In this study, the in-vitro cytotoxic effects of both AgNPs and CuNPs have also been monitored against healthy, regular normal mouse fibroblasts cell line (L929) by means of XTT assay. According to results, the cell viability has not been found significantly affected with increased concentrations (0.1 - 5μg/mL) of nanoparticles; hence it is noticeable and apparent that, none of the phytosynthesized nanoparticles has toxic effect on L929 cells in given concentrations.
Yeşil metal nanopartikül sentezi, kimyasal ve biyokimyasal karakterizasyonu
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Green synthesis; Microwave-assisted synthesis; Antibacterial activity; Cytotoxicity